PENGARUH IMBALAN DAN MOTIVASI KERJA TERHADAP KINERJA DOSEN TETAP YAYASAN STKIP PGRI SUMATERA BARAT - Azwar, Azwar; Zulkifli, Zulkifli (Jurnal Pelangi : Research of Education and Development, 2013)
The purpose of this research is to disclose the influence of reward andwork motivation toward the lecturers’ performance in STKIP PGRI of WestSumatera. There were three hypotheses tested. Firstly, reward influenced thelecturers’ performance. Secondly, work motivation influenced the lecturers’performance. Thirdly, reward and work motivation collectively influenced thelecturers’ performance. The population of this research is 171 lecturers in STKIPPGRI of West Sumatera. Sample is taken by Stratified Proportional RandomSampling technique and they are 63 lecturers. Instrument used for data collectingis a questionnaire of Likert Scale model. The results of the research indicated that(1) reward influences 10% to the lecturers’ performance, (2) work motivationinfluences 12,9% to the lecturers’ performance, and (3) collectively, reward andwork motivation influence 19,1% to the lecturers’ performance. From theseresearch findings, it can be concluded that reward and work motivation are twoimportant factors for increasing the lecturers’ performance.